alguém pode ajuda pfv pra hj ainda
Anexos:
![](https://pt-static.z-dn.net/files/d59/da75097c9a1a8947ebae01ac293cf04b.jpg)
Soluções para a tarefa
Respondido por
1
a) f(-4)= 2*(-4)^2 -6*(-4) -4
f(-4)=2*16+24-4
f(-4)=32+24-4
f(-4)=52
b) g(-3)= -3*(-3)^2 -5*(-3)+1
g(-3)= -3*9+15+1
g(-3)= -27+15+1
g(-3)= -11
f(-4)=2*16+24-4
f(-4)=32+24-4
f(-4)=52
b) g(-3)= -3*(-3)^2 -5*(-3)+1
g(-3)= -3*9+15+1
g(-3)= -27+15+1
g(-3)= -11
Perguntas interessantes
Inglês,
11 meses atrás
Matemática,
11 meses atrás
Ed. Física,
11 meses atrás
Português,
1 ano atrás
Filosofia,
1 ano atrás
Matemática,
1 ano atrás